A Quality Framework for Improving Teaching and Learning Outcomes in a Fully Online MBA program - Ladyshewsky, Richard; Lim, Siew (AACE, 2013)
Academic staff responsible for developing and teaching fully online courses vary in experience. Some may be considered digital immigrants, new to the technology while others are digital natives, comfortable with the technology. Adequate support and quality management at the program level is needed to ensure the courses make the best use of technology and instructors are present for the students. This paper describes a quality initiative at the program level which led to an improvement in overall student satisfaction scores for the online courses. A strategic plan, appropriate support staff, online support resources, data analytic systems, audits and links to performance management processes were used to effect this positive outcome in program quality. The quality initiative engaged staff considered to be digital immigrants and led to an increase in their performance. The need for program based, versus centrally based, quality control systems is discussed.